Assessment of customers’ value-perceptions’ of suppliers’ European pulp offerings - Johansson, Jonas (2014)
Pulp suppliers are acting in a complex and dynamic environment. Branding and differentiation have therefore grown in importance for attracting pulp customer firms. Knowledge about pulp customer firms’ perceptions’ of value has become a key issue so that suppliers can develop valuable offerings.